Readiness in Disclosure of Sustainable Finance through Media and Governance against Firm Value in Indonesia - Ani, Salis Musta (International Journal of Psychosocial Rehabilitation, 2020)
Issues of sustainable finance is currently driving the implementation of Sustainable Development Goals (SDGs) in many countires, including Indonesia. This study examines the readiness for the implementation of sustainable finance by the financial industry in Indonesia through testing the readiness for the disclosure of sustainable finance in the media, as well as governance, and the SRI Kehati (Sustainable and Responsible Investment) index to firm value. Using regression analysis, result shows that one of the governance mechanism and the SRI Kehati index has a significant effect on firm value. This result means that the Financial Services Authority (OJK) as a regulator of the financial industry needs to encourage the application of sustainable finance disclosure in addition to strengthening the implementation of good corporate governance. Investors can consider banking stocks included in the SRI Kehati Index because they can be a driver of firm value.